Dialektika Persona dan Self Kepribadian Tokoh Re dalam Perspektif Jungian - Airvia Yeanisya Gunawan; Resdi Permata Raharjo; Indah Puspitasari (Jurnal Ilmu Sosial, Humaniora dan Seni, 2026)
This study aims to describe the dialectic of persona and self in the Re character's personality structure in the novel Re, by Maman Suherman. Perempuan by Maman Suherman, from the perspective of analytical psychology as developed by Carl Gustav Jung. A qualitative descriptive method with a literary psychology approach was employed. Data were collected by reading and taking notes on Re's narration, dialogue and monologue, which represent personality dynamics. These were analysed using a text-interpretive analysis model. The results show that the interplay between persona and self in Re does not result in identity fragmentation or radical transformation, but instead creates a stable structural balance. The persona of a lesbian sex worker coexists with an active personal value system, ensuring that the self is not diminished by the socially stigmatised role. Tension between the two is evident in the character's emotional fluctuations but does not result in personality disintegration. Re can be said to represent the complexity of the human condition by maintaining continuity of central personality amidst social identity paradoxes, which makes a structural reading of the relationship between persona and self relevant in literary psychological studies.